Social orientation in negotiation: Effects of self-efficacy and self-esteem - Simões, Eduardo (1999)
Studied the relation of self-efficacy, self-esteem, and perception of negotiation issues and utility. Ss included 106 business managers with 3–15 yrs negotiation experience. Data on management and negotiation skills, self-efficacy, self-esteem, and integrative or distributive orientation were obtained by questionnaire. Ss were asked to evaluate several negotiation scenarios. An ANOVA and other statistical tests were used. The results show that high self-efficacy Ss tend to view negotiation scenarios as distributive while low self-efficacy Ss view the scenarios as integrative. The results are discussed in relation to the cognitive miser model (D. H. Ebenbach and K. D. Ebenbach, 1998). DOI: http://dx.doi.org/10.17575/rpsicol.v13i1/2.564